Glutathione: a key frontier of heavy-metal detoxification and tolerance in plants - Swapan Kumar Roy; Mollah Naimuzzaman; Faizur Rahman (Plant Trends, 2023)
Heavy metal (HMs) toxicity is one of the major critical threats for agricultural plants production and global food security. In this current scenario, ecofriendly and hazardous free sustainable crop production strategies for detoxifying and tolerating HMs is imperative. This update study provides the impact of HMs on agricultural plants growth, physiology and yield. Further, this study explores the significance of glutathione (GSH) and phytochelatins (PCs), and series of candidate genes which showed potential role in HMs stress tolerance in diverse plant species. This update study encourages plant breeders or farmers for developing HMs stress tolerant plant production through breeding program. The overall study findings open new avenue of multiomics-assisted plant improvement, and it will help to phytoremediation, clean environment and smart agriculture for sustainable plant production. [Plant Trends 2023; 1(1.000): 33-42]